2016
DOI: 10.1039/c6ra02937j
|View full text |Cite
|
Sign up to set email alerts
|

Ag nanoshell catalyzed dedying of industrial effluents

Abstract: A rapid way to dedye industrial effluents is reported herein using silver nanoshells (Ag-NSs) as a green catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…The slope of the linear plot gives the rate constant of 0.0497 ± 0.0005 s −1 . The larger rate constant with Pd/C‐dots was achieved compared to other reported catalysts (Table S3, Supporting Information) showing the superior catalytic performance in the reduction of EY …”
Section: Resultsmentioning
confidence: 85%
“…The slope of the linear plot gives the rate constant of 0.0497 ± 0.0005 s −1 . The larger rate constant with Pd/C‐dots was achieved compared to other reported catalysts (Table S3, Supporting Information) showing the superior catalytic performance in the reduction of EY …”
Section: Resultsmentioning
confidence: 85%
“…Using these plots, apparent activation energy (Ea), apparent activation enthalpy (▵H*) and apparent activation entropy (▵S*) values were calculated to be 24.5 kJ/mol, 21.9 kJ/mol and −192 J/mol K, respectively. The activation energy obtained by Pd 2 /GO catalyst in Cr(VI) reduction is lower than those found by Pd@γ‐Al 2 O 3 (76.2 kJ/mol), Pd NPs/SiO 2 ‐NH 2 (25.9 kJ/mol) and Pd@TMV (27.3 kJ/mol) catalysts reported for the same reaction . If we assume that the apparent activation parameters calculated from the macroscopic kinetic data given above are relevant to the most critical activation step for Pd 2 /GO catalyzed Cr(VI) reduction mechanism, one can claim that the positive magnitude of the apparent activation enthalpy and large negative value of the apparent activation entropy suggest the presence of an associative reaction step revealing a transition state.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that degradation of methyl orange is classically enhanced in presence of silver nanoparticles due to electron relay effect. 25,26 As presented in Table 1, the rate constant (k) of Rh6G and MO degradation has been calculated for catalyzed reactions as 0.224 min -1 and 0.222 min -1 , and for un-catalyzed reactions as 0.049 min -1 and 0.014 min -1 , respectively.…”
Section: Catalytic Reduction Of Rh6g and Momentioning
confidence: 99%
“…This is due to the increase in the number of surface active sites and increased dye molecules adsorption on the catalyst surface. 25…”
Section: Effect Of Amount Of Catalystmentioning
confidence: 99%
See 1 more Smart Citation